Factors Affecting the Development of Thai Auto Parts Manufacturing Industry for Export (Journal of Namibian Studies : History Politics Culture, 2023)
The study aimed to analyze the obstacles hindering the development of the Thai auto parts manufacturing industry for export, focusing on the second confirmatory factor. Both quantitative and qualitative research methods were used, including in-depth interviews, group discussions, and surveys. The research revealed that the second confirmatory factor identified five main aspects that impede the development of the Thai automotive parts manufacturing industry for exports, with the highest average score. Quantitative research division survey data were collected from 500 executives in the auto parts industry using descriptive, reference, and multiple statistics. The research results revealed that the second confirmatory factor assessed five aspects that impede the development of the Thai automotive parts manufacturing industry for exports with the highest average. The priority of each aspect is as follows:1) Political and economic stability (X ̅  = 4.63). The most important in each item was the international trade war. As a result, global trade slowed down, causing the cost of goods to increase (X ̅  = 4.80). 2) Insufficient resources (X ̅ = 4.56 ). The most important in each item is the personnel's lack of readiness to learn (Growth Mindset) and are unable to adapt to the time frame, and fear of failure (X ̅  = 4.69). 3) Technology impact (X ̅  = 4.52) The most important items are changing cars from combustion engines to zero-emissions cars, causing entrepreneurs to invest more and prepare manpower to be ready with modern innovations (X ̅  = 4.71). 4) Trade and legal barriers (X ̅  = 4.51) The most important item is that the government section has not entered into a free trade agreement, resulting in having to pay customs duties such as VAT import taxes, customs fees, and fees for pre-audit procedures. (X ̅  = 4.64). 5) Management failed (X ̅  = 4.43). The most important items were no indicators suitable for the portfolio to assess the results of achieving the vision to develop and enhance the organization's potential following the same direction (X ̅  = 4.67). The hypothesis testing results found that small, medium, and large businesses pay close attention to factors that impede the development of the Thai automotive parts manufacturing industry for export, differing significantly at the statistical level of 0.05. The second-order confirmatory factor assessment results passed the assessment criteria and were consistent with the empirical data. The chi-squared probability value was 0.263, the relative chi-squared value was 1.041, the concordance index was 0.944, and the root mean squared value of the error estimate was 0.009.